REDD+ as a Public Policy Dilemma: Understanding Conflict and Cooperation in the Design of Conservation Incentives - Conceição, H.R. da; Börner, J.; Wunder, Sven (MDPI, 2018)
Command-and-control policies are often criticized as insufficient to tackle tropical deforestation. Over the past two decades, both academics and policy-makers have promoted incentive-based policies, notably REDD+ (Reduced Emissions from Deforestation and forest Degradation), as attractive alternatives to curb forest loss, while also potentially contributing to the poverty reduction of forest-dwelling populations. Governments have been the driving force behind the largest incentive-based forest conservation programs in Latin America. Many science-based recommendations on how to design effective incentive-based policies have, however, not found much resonance within policy circles. To understand the gap between recommendations and practice, it is important to analyze how these schemes are designed towards achieving environmental and non-environmental outcomes. To this end, we analyzed the comprehensive history of governance dynamics behind two government-led incentive schemes in Ecuador and Peru. We found that electoral interests and bureaucratic politics exerted pressure on policy design teams, which eventually traded off long-term societal efficiency concerns against short-term administrative goals. Priority was often given to non-environmental concerns, due to perceptions of political feasibility, the influence of non-environmental government agencies, and beliefs in particular government roles or public response. These findings are especially relevant for scholars studying the design, implementation and impacts of incentive-based conservation policies, and for practitioners aiming to enhance policy efficiency.